Ethnic minority self-employment - Ken Clark (IZA World of Labor, 2015)
In many countries, ethnic minority groups are over-represented in self-employment compared with the majority community. The kind of work done by minority entrepreneurs can therefore be an important driver of the economic well-being of their ethnic group. Furthermore, growing the self-employment sector is a policy objective for many governments, which see it as a source of innovation, economic growth, and employment. While self-employment might offer economic opportunities to minority groups, it is important to understand the factors that underlie the nature and extent of ethnic entrepreneurship to evaluate whether policy measures should support it.
Keywords: J15; L26; 330; ethnicity; self-employment; entrepreneurship